Do multilevel agricultural innovation platforms support inclusive innovation? Lessons learned from a case study in the Ethiopian highlands - Lema, Zelalem; Bruyn, L.A.L. de; Marshall, G.R.; Roschinsky, R.; Duncan, Alan J. (Informa UK Limited, 2025)
To facilitate smallholder farmers' inclusion within agricultural change processes, agricultural innovation platforms are increasingly being used. Such platforms, which seek to facilitate farmer interactions with diverse actors, are associated with the concept of inclusive innovation. Despite the rhetoric of IPs as inclusive structures, questions persist regarding farmers’ inclusion in decision-making within IPs. This research, based on a livestock innovation case study in the Ethiopian Highlands, examines the role of multilevel IPs in supporting inclusive innovation. Qualitative data collection, timeline analysis of the innovation process and thematic analysis were employed. Results reveal varying levels of farmer inclusion across different phases of the innovation process and IP operational levels. While successful farmer inclusion was apparent in the diagnosis and decentralized learning innovation processes, maintaining inclusivity during the latter phases of the innovation process was difficult, and negatively impacted on farmer-centric outcomes. Decentralized resources, decision-making and reflexive monitoring emerge as crucial in improving smallholder farmers’ inclusion and addressing institutional biases inherent in the technology-push approaches to innovation, especially during farmers’ selection processes that continued to favour better-off or well-connected ‘model’ farmers.